Massage for neonatal pain relief in intensive care units: a scoping review - Thatiane Monick de Souza Costa; Eloysa dos Santos Oliveira; Rodrigo Rhuan Andrade Rocha; Kauanny Vitoria Gurgel dos Santos; Joyce Karolayne dos Santos Dantas; Rodrigo Assis Neves Dantas; Daniele Vieira Dantas (Rev Rene)
Objective: to map the use of massage to relieve neonatal pain during procedures performed in Intensive Care Units. Methods: a scoping review conducted in 11 data sources, following the Joanna Briggs Institute recommendations. The question was: what is the knowledge about the use of massage to relieve pain in newborns during painful procedures in a neonatal intensive care unit? 12 studies were selected for the results. Results: therapeutic massage in newborns is positive in reducing the score on pain scales, decreasing heart and respiratory rates, increasing oxygen saturation, improvements in behavioral status, weight gain, neurological development, shorter crying time and performing the painful procedure. Conclusion: massage/reflexotherapy is effective in reducing neonatal pain in intensive care units, being performed on lower limbs, heel, back or at the procedure site, with light to moderate pressure and an average duration of five minutes.